NAQD MATNAL-HADIS BI 'ILMI TARIKH AL-MUTUN (BAHSUN 'AN 'UMRI AS-SAYYIDAH' AISYAH 'INDA NADZHAR AL'AB AL-HABASYAH WA ITTIKHADZ LU'BAH AL-BANAT FI FATH AL-BARI SYARH SAHIH AL-BUKHARI) - Fuqohak, Mukhamad Agus Zuhurul (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2023)
The study of the history of texts is something that is rarely researched in anything other than what relates to the abrogated, even though many commentators of the hadith have placed this study in other areas, so it is worth examining also in a field other than what relates to the abrogated. Indeed, Sheikh Ibn Hajar Al-Asqalani wrote this study in relation to criticizing the statements that Al-Bukhari mentioned in his book, where Al-Asqalani commented on what Al-Bukhari concluded regarding the rulings and others. This study aims to reveal the study of criticism of the tex of hadith with tarikh al-mutun approach conducted by Syekh Ibnu Hajar in the Fath al-Bari Syarh Sahih al-Bukhari. This research using qualitative method, descriptive-analysis and historical philosophical approach founds that tarikh al-mutun can be traced with awwalu ma kadza, qabla, ba’da, and words with nuances of time such as sanata and ‘ama. Syekh Ibnu Hajar uses tarikh al-mutun to trace the real age of ‘Aishah r.a. in the case of the game of the Habashah and its stuffed toys which some scholars claim are not yet mature. However, Ibnu Hajar found the opposite fact. The benefit of the research is to make tarikh al-mutun not only as nasakh-mansukh data, but also useful for critical matn studies as was done by Syekh Ibnu Hajar. This study has been scattered in the books of hadith commentators, such as Sharh al-Nawawi and others, so it must be researched in order to complete this ideal theory.[Kajian terhadap sejarah nash merupakan hal yang jarang diteliti pada hal lain selain yang berkaitan dengan yang haram, padahal banyak ahli tafsir hadis yang menempatkan kajian ini pada bidang lain, sehingga patut dikaji juga pada bidang selain apa. berhubungan dengan yang dibatalkan. Memang Syekh Ibnu Hajar Al-Asqalani menulis kajian ini dalam rangka mengkritisi pernyataan-pernyataan yang disebutkan Al-Bukhari dalam kitabnya, dimana Al-Asqalani mengomentari apa yang disimpulkan Al-Bukhari mengenai hukum-hukum dan lain-lain. Penelitian ini bertujuan untuk mengungkap kajian kritik teks hadis dengan pendekatan tarikh al-mutun yang dilakukan oleh Syekh Ibnu Hajar dalam Fath al-Bari Syarh Sahih al-Bukhari. Penelitian yang menggunakan metode kualitatif, deskriptif-analisis dan pendekatan filosofis historis ini menemukan bahwa tarikh al-mutun dapat ditelusuri dengan awwalu ma kadza, qabla, ba’da, dan kata-kata yang bernuansa waktu seperti sanata dan ‘ama. Syekh Ibnu Hajar menggunakan tarikh al-mutun untuk menelusuri usia sebenarnya ‘Aishah r.a. dalam hal permainan Habashah dan boneka-bonekanya yang menurut sebagian ulama belum matang. Namun Ibnu Hajar menemukan fakta sebaliknya. Manfaat penelitian ini adalah menjadikan tarikh al-mutun tidak hanya sebagai data nasakh-mansukh saja, namun juga berguna untuk kajian matn kritis seperti yang dilakukan oleh Syekh Ibnu Hajar. Kajian ini telah tersebar di kitab-kitab para ahli tafsir hadis, seperti Syarh al-Nawawi dan lain-lain, sehingga harus diteliti guna melengkapi teori ideal tersebut].